A Dual Swine Challenge With Porcine Circovirus Type 2 (PCV2) and Mycoplasma hyopneumoniae Used to Compare a Combination of Mixable Monovalent PCV2 and Monovalent M. hyopneumoniae Vaccines With a Ready-to Use PCV2 and M. hyopneumoniae Bivalent Vaccine - Yang, Siyeon; Oh, Taehwan; Park, Kee Hwan; Cho, Hyejean; Chae, Chanhee (Frontiers in Veterinary Science, 2020)
The present study evaluated the efficacy of swine vacciation using a combination of mixable monovalents for porcine circovirus type 2 (PCV2) and Mycoplasma hyopneumoniae against a ready-to-use bivalent vaccine under experimental conditions. Pigs at 21 days of age were administered either a combination of two mixable monovalent vaccines or a bivalent vaccine containing PCV2 and M. hyopneumoniae. Vaccination was followed with an M. hyopneumoniae challenge at 42 days of age (-14 days post challenge, dpc) and a PCV2d challenge at 56 days of age (0 dpc). Each vaccinated and challenged group was compared with the unvaccinated and challenged group for clinical, microbiological, immunologic, and pathologic differences. Clinically, two vaccinated and challenged groups showed minimal respiratory diseases that was characterized by occasionally coughing and sneezing. A significant difference was not calculated in the average daily weight gain, nasal shedding of M. hyopneumoniae, and pathological lesions between two vaccinated and challenged groups. A combination of two monovalent vaccines mixed into a combo prior to vaccination followed by challenge resulted in increased numbers of PCV2d-specific interferon-γ secreting cells at 21 dpc and a significant reduction in PCV2d viremia at 14 dpc when compared with the ready-to-use bivalent-vaccinated and challenged groups. These results offer supporting evidence that vaccination during the weaning to finishing period against M. hyopneumoniae and PCV2 is efficacious for controlling diseases caused by these two pathogens.